Expression of class II transplantation antigen on vascular smooth muscle cells in human atherosclerosis. - Jonasson, L (1985)
A large proportion of the cells of the human atherosclerotic plaque is assumed to be derived from medial smooth muscle cells. In contrast to these, the cells of the plaque have the capacity to accumulate lipid, and they also proliferate at a higher rate than medial cells. It has therefore been suggested that smooth muscle cells undergo a change of phenotype during atherogenesis, but there has been no evidence for such a change on the molecular level. We have now analyzed carotid artery plaques using a battery of antibodies against cell surface and cytoskeletal antigens, and found that most of the cells express the class II transplantation antigen (Ia antigen) HLA-DR. Also, the beta chain of HLA-DR was detected by immunoblotting of plaque extracts with the OKIa1 monoclonal antibody. HLA-DR is normally present on cells of the immune system, but only 60% of the DR-positive cells of the plaque reacted with monoclonal antibodies specific for macrophages and lymphocytes. Many of the remaining DR-positive cells contained the muscle-specific intermediate filament protein, desmin. This indicates that smooth muscle cells of atherosclerotic plaques express DR antigen. In contrast, very few DR-positive cells were found in normal human arteries. This suggests that expression of class II antigen is part of a phenotypic change in smooth muscle cells in atherosclerosis.